Proposed method for digital image normalisation - Omar Muayad Abdullah (International Journal Of Electrical Engineering and Inteligent Computing, 2025)
Image normalisation is considered as an important factor in the scope of image enhancement. In this research paper we introduced a proposed model used for image normalisation (contrast stretching) through two phases, design phase and implementation phase. First, the design phase consists of the proposed formulas used for processing the degraded images, where the first formula represents the processing of the darked image illuminations and the second one represents the processing of the highlighted image illuminations, the second part of the design phase we determined which formula has to be used for processing the image degradation. So here for processing this part, we used a K-means clustering machine learning algorithm. The second part is the implementation phase which is used for applying the proposed model and the final step comparing the obtained results with other determined normalisation algorithms.